Multimedia Interaktif Macromedia Flash 8 Berbasis Pendekatan Konstruktivisme Pada Pembelajaran IPAS di Sekolah Dasar - Luther, Nober; Erita, Yeni (Universitas Negeri Padang, 2023)
This research is motivated by the use of technology-based media which is rarely used in elementary schools. This study aims to develop Macromedia Flash 8 Interactive Multimedia Based on Constructivism Approach in Science Learning in Grade IV Elementary School. The type of research used is development (R&D) with the ADDIE model which consists of 5 stages (analysis, design, development, implementation, and evolution). The results of research on developing teaching materials have a very valid validity level, media validity is 85%, material validity is 91.25%, and language validity is 92.5%. Results of the practicality test at the pilot school SDN 01 UKS. Teacher response questionnaire 92% and students 92%. At the school where the study was at SDN 29 UKU, the teacher response questionnaire was 96%, the students were 95%. At SDN 25 ATS, the teacher response questionnaire was 96%, the students were 94%. The results of the effectiveness of the test schools at SDN 01 UKS and the schools where the research was conducted were at SDN 29 UKU and SDN 25 ATS in the pre-test and post-test results. With that the use of